A Tramp Abroad $1 (BVolume 06s - Twain, Mark, 1835-1910 (Salt Lake City, UT : Project Gutenberg, 2004)
"A Tramp Abroad $1 (BVolume 06" by Mark Twain is a travel narrative published in 1880. This sixth volume continues Twain's humorous journey through Europe with his companion Harris, as they traverse Switzerland, eastern France, and northern Italy. The narrator plays the quintessential American tourist, confidently interpreting foreign customs while completely misunderstanding them. Between travel accounts, Twain weaves unrelated tales, German legends, and satirical essays. The work combines autobiography with fiction, creating comedy through the travelers' bewildered reactions to continental life. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Tramp_Abroad
Illustrated.
Release date is 2004-06-18
Produced by Anonymous Volunteers, John Greenman and David Widger
Keywords: Humorous stories; Europe -- Fiction; Americans -- Europe -- Fiction; Walking -- Fiction